Les jardins et l’esthétique de Kobori Enshū : La structure du kirei sabi - Yama.uchi Tomoki (Projets de Paysage)
In this article, we shall examine the aesthetics of Kobori Enshū (1579-1647) who, as the project manager of the shogunat’s official buildings, conceived numerous gardens and buildings between the late 15th century and the early 16th century. Because the relics of Kobori Enshū’s works show the frequent use of straight lines and a very clear structure, they are put into the aesthetic category called kirei sabi. His gardens, which display a geometric structure, contrast with the previous Japanese traditional gardens, and one may see the influence of the landscape techniques from China or Europe. Until then, Kobori Enshū was considered as the one who had made the synthesis of different cultural spheres; but this interpretation alone is not satisfying to explain the novelty of his aesthetics. In this article, we aim at explaining that the special feature of Kobori Enshū’s art is not in the synthesis but, on the contrary, that it lays in the randomness and the movement linked to the meeting of different cultural spheres – in other words, to the plurality which is inherent in opposition.